2014
DOI: 10.1007/s00204-014-1374-8
|View full text |Cite
|
Sign up to set email alerts
|

Ninety-day oral toxicity studies on two genetically modified maize MON810 varieties in Wistar Han RCC rats (EU 7th Framework Programme project GRACE)

Abstract: The GMO Risk Assessment and Communication of Evidence (GRACE; www.grace-fp7.eu) project is funded by the European Commission within the 7th Framework Programme. A key objective of GRACE is to conduct 90-day animal feeding trials, animal studies with an extended time frame as well as analytical, in vitro and in silico studies on genetically modified (GM) maize in order to comparatively evaluate their use in GM plant risk assessment. In the present study, the results of two 90-day feeding trials with two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 13 publications
8
59
0
Order By: Relevance
“…Many types of Bt-crops have been commercialized worldwide, triggering concerns about their potential impact on the health of humans and livestock. A large number of feeding studies have shown that the Cry proteins expressed by Bt-crops are non-toxic to humans and mammals (Kılıç et al, 2008;Buzoianu et al, 2013;Zeljenková et al, 2014). Diets containing Bt-corn had no deleterious effects on weight gain and carcass yields of broilers (Brake et al, 2003;Taylor et al, 2003;McNaughton et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many types of Bt-crops have been commercialized worldwide, triggering concerns about their potential impact on the health of humans and livestock. A large number of feeding studies have shown that the Cry proteins expressed by Bt-crops are non-toxic to humans and mammals (Kılıç et al, 2008;Buzoianu et al, 2013;Zeljenková et al, 2014). Diets containing Bt-corn had no deleterious effects on weight gain and carcass yields of broilers (Brake et al, 2003;Taylor et al, 2003;McNaughton et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Besides my alleged, but nonexisting, ties to industry, Bauer-Panskus and Then (2014) suggest yet another 'conflict of interest' of myself and in a strange twist use this alleged conflict to request withdrawal of the article of Zeljenková et al (2014): In one of my previous publications (Hengstler et al 2011), coauthors have worked in a chemical company or as industry consultants. What a surprise that this publication was chosen to construct a conflict of interest against me, as it represents a consensus paper of the Advisory Committee of the German Society of Toxicology (GT).…”
mentioning
confidence: 99%
“…Recently, the results of a 90-day feeding study with genetically engineered plants have been published in our journal (Zeljenková et al 2014). The subchronic study showed that engineered maize at a level of up to 33 % in the diet did not cause adverse effects in rats.…”
mentioning
confidence: 99%
See 2 more Smart Citations